Institutional gaps in managing multiple: European projects co-funded by public and private institutions - Monika Mačiulienė; Aelita Skaržauskienė; Dick Botteldooren (Contemporary Economics, 2018)
The purpose of this paper is to compare perceptions on drivers of managing multiple European co-funded projects among public and private institutions from Romania, and determine which dimensions of multi-project management optimization have the greatest impact on institutional financial stability and organizational learning. Data were collected using an online questionnaire administrated to two convenience samples of 100 public institutions, and 100 private organizations from Romania, involved in managing multiple European co-funded projects. Multi-project management optimization was measured using two dimensions: the relational dimension for governance of multiple projects and the regulative dimension. Data were analyzed by using confirmatory factor analysis, ANOVA and linear regression. In the private organizations sample, relational dimension was the most important predictor of organizational learning, while regulative dimension was the most important predictor of financial stability in the sample of public institutions.
Keywords: H43; O22; 330; multiple project management; financial stability; organizational learning; project management governance